COVID-19 Pandemic and Increased Violence Against Women in Uganda - Milliam, Kiconco (Advances in Social Sciences Research Journal, 2022)
This paper has used secondary review methodology to explore the link between COVID-19 pandemic and increased violence against women in Uganda. Data from articles, newspapers, government documents and Non-Governmental Organizations reports have been used in coming up with this paper. The paper begins with a general discussion of violence against women at a global level and in Uganda. This is followed by the discussion of how disasters and pandemics expose women and girls to physical, sexual, emotional and psychological violence. A discussion on how COVID-19 pandemic is to some extent similar to the earlier disasters such as Ebola in causing a spike in violence against women has also been made. This is, partly, due to associated lockdowns and other preventive measures that confine women in the same household with the abusers and prevent them from seeking help. It has also been shown that COVID-19 pandemic diverted governments’ effort from violence against women and led to other social, economic and psychological stresses linked to violence. The paper has further shown that before COVID-19 pandemic struck, Uganda was regarded as a country with one of the highest cases of violence against women. How this violence has been amplified by COVID-19 pandemic has been discussed in this paper. Finally, the paper has recommended a multi-sectoral approach to addressing violence against women and the need for including violence against women in the future plans against pandemics.